A Portable Emissions Measurement System (PEMS) study of NOx and primary NO2 emissions from Euro 6 diesel passenger cars and comparison with COPERT emission factors. (November 2016) - O'Driscoll, Rosalind; ApSimon, Helen M.; Oxley, Tim; Molden, Nick; Stettler, Marc E.J.; Thiyagarajah, Aravinth
Abstract: Real world emissions of oxides of nitrogen (NOx ) often greatly exceed those achieved in the laboratory based type approval process. In this paper the real world emissions from a substantial sample of the latest Euro 6 diesel passenger cars are presented with a focus on NOx and primary NO2 . Portable Emissions Measurement System (PEMS) data is analysed from 39 Euro 6 diesel passenger cars over a test route comprised of urban and motorway sections. The sample includes vehicles installed with exhaust gas recirculation (EGR), lean NOx traps (LNT), or selective catalytic reduction (SCR). The results show wide variability in NOx emissions from 1 to 22 times the type approval limit. The average NOx emission, 0.36 (sd. 0.36) g km −1, is 4.5 times the Euro 6 limit. The average fraction primary NO2 (fNO2 ) is 44 (sd. 20) %. Higher emissions during the urban section of the route are attributed to an increased number of acceleration events. Comparisons between PEMS measurements and COPERT speed dependent emissions factors show PEMS measurements to be on average 1.6 times higher than COPERT estimates for NOx and 2.5 times for NO2 . However, by removing the 5 most polluting vehicles average emissions were reduced considerably. Highlights: Largest Euro 6 PEMS study to date with 39 vehicles. Detailed analysis of fraction primary NO2 and absolute NO2 emissions. Analysis of EGR, LNT and SCR NOx control technologies. Comparison between real world emissions and COPERT emissions factors. Comparison of urban and motorway driving and effect of acceleration on NOx emission.